Influence of age on the reproductive biology of female Schizopyge niger (Heckel, 1838) inhabiting Dal lake, Kashmir: Reproductive biology of Schizopyge niger - Rashid, Ifrah; Shah, Tasaduq H.; Bhat, F. A.; Abubakr, Adnan; Bhat, Bilal A; Mushtaq, Syed Talia; Jahan, Ahali; Wali, Asifa (Journal of the Inland Fisheries Society of India, 2023)
Schizopyge niger, a prized indigenous cyprinid fish of Kashmir valley, contributes significantly to the fish catch from the valley. They are highly valued fish with high demand locally and are preferred over most other native fish species. The study was aimed at investigating the effect of age on gonadotropins (GtHs), gonadosomatic index (GSI) and hepatosomatic index (HSI) of female Schizopyge niger. A total of 106 samples at random were collected from Dal Lake for this study during spawning season. Age of fish ranged from 2+ years to 6+ years with an average length from 119.39 to 292.17 mm. A significant correlation (p 0.05). Hepatosomatic index (HSI) ranged from 0.47% to 2.63% and increased with age of fish. A positive correlation was observed between HSI and age (R2= 0.7004; p> 0.05). This study will provide baseline information for fisheries biologists about age related variations in the reproductive parameters of this species.